Distribution of Hot Springs Blawan-Ijen Based on Geoelectrical Resistivity Data - Ika Karlina Laila Nur Suciningtyas; Sukir Maryanto; Arif Rachmansyah (Natural B, Journal of Health and Environmental Sciences, 2013)
Geothermal energy is a source of heat that occurs naturally in the subsurface. One of the geothermal potential in East Java is in the Blawan that known as geothermal Blawan - Ijen. To find a geothermal potential of an area we have to do some research on subsurface conditions. Research using geoelectric resistivity method has been performed to estimate the distribution of hot springs. The study, conducted in May 2013 showed that there are 21 hot springs manifestations in Blawan - Ijen. Each of these hot springs have a temperature less than 50 °C. Data of geoelectric resistivity divided into 3 parts, resistivity values less than 40 ohm.meter indicated by the color blue , the color green for the resistivity value between 40-1280 ohm.meter and the color orange for values more than 1280 ohm.meter. Geothermal distribution that contained in Blawan is diffused follow existing fracture. Direction of hot springs are heading to the Northeast that following the river flow. The heat carrier layer is permeable layer that have resistivity values less than 40 ohm.meter.